2015
DOI: 10.1016/j.cct.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Study design, intervention, and baseline characteristics of a group randomized trial involving a faith-based healthy eating and physical activity intervention (Walk by Faith) to reduce weight and cancer risk among overweight and obese Appalachian adults

Abstract: Background Increased prevalence of overweight and obesity among Appalachian residents may contribute to increased cancer rates in this region. This manuscript describes the design, components, and participant baseline characteristics of a faith-based study to decrease overweight and obesity among Appalachian residents. Methods A group randomized study design was used to assign 13 churches to an intervention to reduce overweight and obesity (Walk by Faith) and 15 churches to a cancer screening intervention (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Faith institutions have the potential to be important partners in the effort to address obesity and related health conditions among African American adolescent males as churches have been rich settings for weight loss and weight gain prevention interventions targeting African American adults. 3942,4951 However, setting is only a starting point. We believe that faith-oriented concepts and tenets such as religiosity and spirituality can have implications for health and health behaviors and we sought to explore the relationship between spirituality and religiosity and weight maintenance among African American adolescent males using data from the JHS-KIDS pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…Faith institutions have the potential to be important partners in the effort to address obesity and related health conditions among African American adolescent males as churches have been rich settings for weight loss and weight gain prevention interventions targeting African American adults. 3942,4951 However, setting is only a starting point. We believe that faith-oriented concepts and tenets such as religiosity and spirituality can have implications for health and health behaviors and we sought to explore the relationship between spirituality and religiosity and weight maintenance among African American adolescent males using data from the JHS-KIDS pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of interest was change in participant weight from baseline to 12 months, and secondary outcomes included changes in blood pressure (systolic), physical activity (measured by daily steps recorded by pedometers worn by participants and physical activity questionnaires), and diet (measured by a validated food frequency questionnaire). Details of the study design and theoretical framework for the interventions have been described elsewhere [15]; the study population, intervention, assessments, and outcomes are briefly described below.…”
Section: Methodsmentioning
confidence: 99%
“…Only a limited number of studies have been conducted to delineate the causes of observed health disparities, with the majority of research and outreach programs to date focused on lifestyle and behavioral risk factors. For example, obesity rates are particularly high in Appalachia; consequently, several cancer prevention programs have focused on increasing physical activity and promoting healthy eating, alongside increased screening initiatives in the broader region [17][18][19]. Reduced access to and utilization of health care remains a complicating issue in Appalachia that likely results in delayed diagnosis, suboptimal care, and ultimately worse outcomes from cancer, diabetes and cardiovascular and respiratory disease [20].…”
Section: A History Of Health Disparitiesmentioning
confidence: 99%